Proceso administrativo y su incidencia en la efectividad de las actividades docentes del Instituto Tecnológico Superior Ciudad de Valencia - Figueroa Palacios, Tatiana Julexi (2017)
With the present investigative work it is tried to demonstrate the relevance that has to raise a guide for the qualification to the administrative personnel and teachers, thus to be able to increase the effectiveness in educational activities of the superior technological institute "City of Valencia" period 2017, since this It will serve as a great help to solve the problems that this institution is presenting, through seminars where the knowledge of the teachers is strengthened and strengthened and in this way provide a quality education. The population surveyed in the present investigation is made up of 29 participants who are divided into 23 teachers, 4 administrative and 2 authorities, because it is a small population, sampling will not be applied and the total population will be worked on. To carry out this research study the use of the following methods and very important research techniques were used, such as: Direct observation and the survey which were directed to the aforementioned population In order to achieve these objectives, information was gathered from various sources describing the administrative processes and the role or activities that teachers must perform